“O que você quer ser quando crescer?” Estereótipos de gênero e perspectivas profissionais de crianças - Macêdo, Mayara da Vera Cruz (Universidade Federal de São Carlos, 2025)
Several researchers have studied the effects of gender stereotypes on children's development and their influence on future career choices, such as encouraging boys to become engineers and girls to become teachers. The literature has shown how gender stereotypes tend to exaggerate perceptions of abilities and potential, particularly in educational and professional contexts, thereby contributing to unequal treatment and opportunities for men and women and perpetuating social inequalities. The primary objective of this study was to contribute to the discussion by investigating a potential correlation between gender stereotyping and school-aged children's preferences for their future jobs. The participants were 23 children from the 1st and 3rd grades of two public elementary schools in a city of São Paulo, Brazil. To measure gender stereotyping, the Preschool Occupations, Activities, and Traits (POAT) Scale was used. This instrument assesses how stereotypical participants are through two subscales: the Attitude Measure (AM), which assesses children's beliefs about what boys and girls can do, and the Personal Measure (PM), which assesses their self-perceptions concerning gender stereotypes. In addition, the children answered a question about their future career aspirations (“What do you want to be when you grow up?”). The results showed that most participants scored moderate levels of gender stereotyping (52.2%). An analysis of variance (ANOVA) revealed no significant differences between the two age groups. However, participants scored significantly higher on the personal measure (PM) compared to the attitude measure (AM), suggesting that although children may believe that boys and girls can engage in a variety of activities, they still tend to choose gender-congruent options for themselves. Even so, among the 18 children who presented high scores on the PM subscale, only 6 of them chose jobs stereotypically associated with their gender, which may indicate a degree of flexibility in their internalized stereotypes. Despite practical limitations, such as the small and uneven sample size of this research, these findings suggest that gender stereotypes continue to influence children’s attitudes and expectations. Nonetheless, when asked broadly about their career aspirations, children may demonstrate greater flexibility, therefore pointing out the importance of more gender-neutral and inclusive educational approaches.
"What do you want to be when you grow up?" Gender stereotypes and children's professional perspectives
Keywords: Estereótipos de gênero; Desenvolvimento infantil; Perspectivas profissionais; CIENCIAS HUMANAS::PSICOLOGIA